Carcinoma of the Rectum: A Clinicopathological Evaluation of Patients in Tertiary Care Hospitals - Hossain, Mohammad Arif; Bhuiyan, Md Jahangir Kabir; Talukdar, Tutul; Quader, Feroze (Journal of Surgical Sciences, 2020)
Background: Colorectal carcinoma is the fourth most commonly diagnosed cancer and the third leading cause of cancer deaths worldwide. The rectum is the most frequent site involved. The disease is no less common in our country in comparison to western world. The aim of this study was to determine the incidence and to review the clinicopathological aspects of carcinoma rectum in different ages in our country. Methods: This is a prospective observational study which includes 50 cases of carcinoma rectum which were admitted under different surgical units of Dhaka Medical College Hospital and Bangabandhu Sheikh Mujib Medical University during the period of November 2007 to December 2008. Results: The present study showed maximum incidence of carcinoma rectum in the age group 21-30 years. Next common age group was 31-40 years. Incidence declined after 60 years. Majority of victims were male giving a male to female ratio of 1.17:1. As regards the mode of clinical presentation, most patients presented with bleeding per rectum. Majority of patients in this study was moderately anaemic. Curative resection was possible in 54% cases, palliative resection in 38% and palliative end colostomy was done in 4% cases. Only 2% mortality was reported in this study. Histopathological grading showed that poorly differentiated adenocarcinoma of rectum was more common in younger age group. Conclusion: Younger patients with carcinoma rectum have several distinct clinicopathological features. Since early diagnosis is essential to improve the cure rate for carcinoma rectum, all known procedure tools must be used to detect carcinoma of the rectum in an early stage, in addition to periodic selective investigations of high-risk group. Journal of Surgical Sciences (2020) Vol. 24 (1) : 15-20